Normothermia in Patients With Sepsis Who Present to Emergency Departments Is Associated With Low Compliance With Sepsis Bundles and Increased In-Hospital Mortality Rate*. Issue 10 (October 2020) - Park, Sunghoon; Jeon, Kyeongman; Oh, Dong Kyu; Choi, Eun Young; Seong, Gil Myeong; Heo, Jeongwon; Chang, Youjin; Kwack, Won Gun; Kang, Byung Ju; Choi, Won-Il; Kim, Kyung Chan; Park, So Young; et al.
Abstract : Objectives: To investigate the impact of normothermia on compliance with sepsis bundles and in-hospital mortality in patients with sepsis who present to emergency departments. Design: Retrospective multicenter observational study. Patients: Nineteen university-affiliated hospitals of the Korean Sepsis Alliance participated in this study. Data were collected regarding patients who visited emergency departments for sepsis during the 1-month period. The patients were divided into three groups based on their body temperature at the time of triage in the emergency department (i.e., hypothermia [< 36°C] vs normothermia [36–38°C] vs hyperthermia [> 38°C]). Interventions: None. Measurements and Main Results: Of 64, 021 patients who visited emergency departments, 689 with community-acquired sepsis were analyzed (182 hyperthermic, 420 normothermic, and 87 hypothermic patients). The rate of compliance with the total hour-1 bundle was lowest in the normothermia group (6.0% vs 9.3% in hyperthermia vs 13.8% in hypothermia group; p = 0.032), the rate for lactate measurement was lowest in the normothermia group (62.1% vs 73.1% vs 75.9%; p = 0.005), and the blood culture rate was significantly lower in the normothermia than in the hyperthermia group ( p < 0.001). The in-hospital mortality rates in the hyperthermia, normothermia, and hypothermia groups were 8.5%, 20.6%, and 30.8%, respectively ( p < 0.001), but there was no significant association between compliance with sepsis bundles and in-hospital mortality. However, in a multivariate analysis, compared with hyperthermia, normothermia was significantly associated with an increased in-hospital mortality (odds ratio, 2.472; 95% CI, 1.005–6.080). This association remained significant even after stratifying patients by median lactate level. Conclusions: Normothermia at emergency department triage was significantly associated with an increased risk of in-hospital mortality and a lower rate of compliance with the sepsis bundle. Despite several limitations, our findings suggest a need for new strategies to improve sepsis outcomes in this group of patients. Abstract : Supplemental Digital Content is available in the text.